Brain Activity in Different Brain Areas of Patients With Dry Eye During the Female Climacteric Period According to Voxel-Based Morphometry - Hu, Meng-Yan; Zhang, Li-Juan; Kang, Min; Pan, Yi-Cong; Ge, Qian-min; Li, Qiu-yu; Yang, Lin; Pei, Chong-Gang; Shao, Yi (Frontiers in Neurology, 2022)
We aim to investigate potential morphological alterations of the brain in female climacteric patients with dry eye (DE) and their relationship to behavioral performances. Twenty-five female patients with DE disease during the female climacteric period and 25 age and education-matched healthy controls (HCs) underwent magnetic resonance imaging. Imaging data were analyzed using voxel-based morphometry (VBM) to identify group differences in DE patients and HCs. Compared with HCs, patients with DE during the female climacteric period had significantly decreased VBM in the Putamen_L, Thalamus_R, Precuneus_L, Frontal_Sup_R, Cingulum_Mid_L, and Frontal_Mid_L. There was increased VBM in the Temporal_Pole_Sup_R, Precentral_R and Insula_L. Receiver operating characteristic curve analysis indicated that the VBM method has clear potential for diagnosis of DE patients during the climacteric period. Correlation analysis found a negative correlation between the VBM values of the Putamen_L and the anxiety score (AS) and depression score (DS), a positive correlation was found between VBM values of the Temporal_Pole_Sup_R and AS. Moreover, VBM values in the Cingulum_Mid_L were positively correlated with AS and DS. These results revealed abnormal spontaneous activity in the brain regions of patients with DE during the climacteric period, which may indicate underlying pathological mechanisms. These results may help to advance clinical treatments.